The effect of multiple S(Δ) periods on responding on a fixed-interval schedule - Dews, P. B. (1962)
The effect of repeated interruption of FI responding by short S(Δ) presentations on the pattern of increasing frequency of responding through the interval has been studied. Although the S(Δ) profoundly changed the pattern of responding during their presentation, the general scalloped pattern of FI responding survived. The implication of these findings for understanding the role of chaining of responses in FI patterns is discussed. It is suggested that chaining is not a necessary condition for the scalloped pattern.